Perbandingan hasil belajar siswa menggunakan emodul berbasis CTL dengan buku teks fisika kelas X pada materi hukum newton tentang gerak dan gravitasi di SMA Negeri 12 Padang - Ria Monica; Yenni Darvina; Desnita Desnita; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2020)
The 2013 curriculum requires the use of diverse learning resources and can help students learn independently. Especially for physics learning that has characteristics connecting learning material with everyday contexts or contextual nature. The fact found in the field, that the learning resources used are textbooks and do not use everyday contexts. CTL-based e-modules can represent learning resources that are suitable for learning physics and help students learn independently. The purpose of this study was to determine the differences in student learning outcomes using CTL-based E-modules with physics textbooks in SMA Negeri 12 Padang. This type of research is a quasi-experimental research. Sampling using a purposive sampling technique. The sample in this study consisted of two sample classes with a total of 36 students each class. The results of the study were conducted normality test and homogeneity test, it was proven that the data of both sample classes were normally distributed and homogeneous. Two similarity tests of the average for all aspects of learning outcomes, carried out at a real level of 0.05 and degrees of freedom dk 70 for all three aspects with each ttabel is 1.9900 obtained on the knowledge aspect of thitung is 2.9977, on the attitude aspect thitung is 3.4425 and in the skill aspect thitung is 2.2901. From these results it is known that thitung> ttabel. This means that classes using CTL-based E-modules have higher learning outcomes than classes that use physics textbooks. Therefore, it can be concluded that there is a significant difference in the average learning outcomes of the use of CTL-based E-modules in Class X students of SMA Negeri 12 Padang.